Prevrashcheniye 'fritsev' - Kukryniksy (1943)
Hitler pointing forward to shuddering soldiers arrayed in front of rows of swastikas and graves Original title: Превращение «фрьцев». Suggested translation: The transformation of 'the Fritz' PO-0053